Analysis of Preservice Teachers' Ability to Develop TPACK Integrated Learning Tools - Sridana, Nyoman; Novitasari, Dwi; Magfirah, Nurul (Pendidikan Matematika FKIP Universitas Mataram, 2024)
This study aims to analyze the ability of preservice mathematics teachers at University of Mataram to develop learning tools such as powerpoint presentations and student worksheets integrated with TPACK to foster 21st-century skills. The study was conducted in Micro Teaching courses with 14 students as research subjects. Data collection techniques included assessment sheets and interviews. The results shows that the learning tools created by preservice teachers are quite capable of supporting 21st-century skills. The ability of preservice mathematics teachers to develop TPACK-integrated powerpoint presentations overall has an average score of 2.43, which is categorized as moderate. The ability of preservice mathematics teachers to develop worksheets integrated with TPACK overall has an average score of 3.59, which is categorized as high. Based on interview results, it was found that applying the TPACK approach in learning tools is very important, as it can create engaging, interactive learning and facilitate students' understanding of the material.